Forecast Model to Estimate Energy Stock Price in Colombia - Gómez-Cano, Lucero; Catalina-Cuellar, Sandra; Méndez-Vargas, Raphael (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The aim of this work is to propose a statistical model to forecast the price spot of energy on the stock electric market in Colombia, incorporating the effect of some variables that have impact on its formation. To do it, we proceed with a contextualization of the electricity market in Colombia, because its structure and operating model determine the formation of market prices, among which the price spot of energy has the highest volatility. To identify the forecasting model, the Box-Jenkins methodology of time series is used and the best SARIMA, SARIMAX and VAR model is proposed, from which the corresponding forecasts and analysis of results are made.